Independent load carrying and measurement manipulator robot arm for improved payload to mass ratio. (October 2018) - Merckaert, Kelly; De Beir, Albert; Adriaens, Nick; El Makrini, Ilias; Van Ham, Ronald; Vanderborght, Bram
Abstract: Recently, the development of collaborative robots that have to work in a cooperative way with humans, has become an important trend both in academia and in the industry. Thereby, safety has increasingly become an essential research aspect. Today, the main techniques to ensure safety are based on reducing 1) the stiffness of the actuators and/or links, 2) the speed of the robot when it approaches humans or obstacles, and 3) the weight of the robot. In all these techniques, the robot's end-effector position is measured by position sensors on the joints, whereby the robot's limbs have to be as rigid as possible. This method has as possible drawbacks that the limbs have to carry unnecessary load (i.e. the robot's weight), and that the position errors increase with increased payload so that the robot can only be used for low payloads. To tackle these problems, we proposed a novel error compensation method based on the use of an additional measurement arm in parallel with the main load bearing arm, whereby the two arms are only coupled between the base and the end-effector. We designed a proof of concept robotic arm and validated the feasibility of our method. This paper presents the End-Effector Position Measuring (EEPM) method and introduces the Independent Load And Measurement Arm (ILAMA) to demonstrate the EEPM concept. With this novel method, the robot can be designed by strength instead of by stiffness. As a consequence, the weight of the limbs can drastically be reduced and the payload to mass ratio can be increased to a value that is bigger than one, while preserving the high end-effector position accuracy, as shown in the experiments. These advantages make the EEPM method very promising to use in collaborative robots or in mobile robot arms. Future works will investigate the feasibility of the proposed concept for real industrial robots with 6 to 7 DOF. Highlights: A novel mechanical error compensation method is proposed. An additional measurement arm is used in parallel with the main load bearing arm. The measurement arm is load independent and measures the end-effector position. The load bearing arm can be designed by strength instead of by stiffness. The payload to mass ratio can be increased and the position errors can be reduced.